(untitled) (The International Journal for Scientific Research, 2024)
The study aimed to explore the impact of organizational commitment dimensions (affective commitment, normative commitment, and continuance commitment) on administrative innovation, mediated by ethical leadership, at the Saudi Standards, Metrology, and Quality Organization (SASO). The study utilized a descriptive-analytical approach and employed questionnaires to measure the study variables. The final sample consisted of 293 employees from the organization. The study reached several important findings, including that organizational commitment in its three dimensions (affective, normative, and continuance) positively influences the performance and administrative innovation of the employees. Additionally, the results showed that ethical leadership enhances organizational commitment and encourages creative thinking. The study recommended the development of training programs to enhance organizational commitment and promote ethical leadership among employees at the organization. It also recommended adopting policies that support creative thinking and providing incentives for employees who contribute new and innovative ideas. Furthermore, it emphasized the need to improve the organizational environment to be supportive of innovation and creativity and to promote transparency and integrity at all levels of the organization.